THE MANDATORY VIDEO RECORDING OF INTERROGATIONS IN UZBEKISTAN: PERSPECTIVES AND ADVANTAGES (TSUL LEGAL REPORT, 2026)
This paper describes the issue of video recording interrogations, providing a thorough analysis of the experiences of several foreign countries, including Japan, the US, Canada, and Poland, as well as the opinions of scholars in this field. The paper describes two main categories of advantages the video recording of interrogations offers, both of which contain detailed analysis of several factors that contribute to the establishment of mandatory video recording of interrogations in Uzbekistan. The first category includes benefits in ensuring human rights during interrogations, and the second category focuses on the compliance of interrogations with the norms and provisions of criminal procedural legislation. Although there may be potential disadvantages to the video recording of interrogations, the authors have put a strong emphasis on the advantages this innovation offers and provided specific examples for each advantage. The authors have also suggested adding new provisions and amending the existing ones regarding the mandatory recording of interrogations in the Criminal Procedure Code of Uzbekistan in line with the analysis of foreign countries’ experiences in this field.